2021
DOI: 10.1038/s41598-021-92781-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome survey of big cats (Genus: Panthera) identifies novel microsatellites of utility in conservation genetic study

Abstract: Big cats (Genus: Panthera) are among the most threatened mammal groups of the world, owing to hunting, habitat loss, and illegal transnational trade. Conservation genetic studies and effective curbs on poaching are important for the conservation of these charismatic apex predators. A limited number of microsatellite markers exists for Panthera species and researchers often cross-amplify domestic cat microsatellites to study these species. We conducted data mining of seven Panthera genome sequences to discover … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…A similar study revealed 54% of microsatellite similarity between horse and humans (Farber and Medrano 2004). During the complete genome sequence analysis of large cats, twelve microsatellite loci were identified, which is useful to mitigate the conservation of related species, such as tigers, snow leopards, and lions (Hyun, Pandey et al 2021). The study of microsatellite presence and its distribution in mammalian genomes has gained much attention, compared with the Ostreidae family.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study revealed 54% of microsatellite similarity between horse and humans (Farber and Medrano 2004). During the complete genome sequence analysis of large cats, twelve microsatellite loci were identified, which is useful to mitigate the conservation of related species, such as tigers, snow leopards, and lions (Hyun, Pandey et al 2021). The study of microsatellite presence and its distribution in mammalian genomes has gained much attention, compared with the Ostreidae family.…”
Section: Introductionmentioning
confidence: 99%